Dickens and the Short Story - Thomas, Deborah A. (University of Pennsylvania Press, 2016)
Ranging from "flights of fancy" to literary masterpieces, Dickens' short stories contained artistic experiments that inspired fuller developments in his novels. Yet the short stories have been all but overlooked in critical discussions. Deborah A. Thomas focuses directly on this body of work, tracing three stages of development.